Haemostatic activation in post-menopausal women taking low-dose hormone therapy: Less effect with transdermal administration? - Brosnan, Jeanette F.; Sheppard, Brian L.; Norris, Lucy A. (Thrombosis and Haemostasis, 2007)
Hormone therapy (HT) increases the risk of cardiovascular and thromboembolic disease in post-menopausal women. Recent studies have suggested that prothrombotic mechanisms are likely to be involved. Transdermal HT avoids the first-pass effect of oestrogen in the liver and may have a less marked effect on the haemostatic system than equivalent oral preparations. The majority of studies have compared HT preparations that have different formulations as well as routes of administration. We investigated changes in the haemostatic system in post-menopausal women using two pharmacologically similar HT preparations, which differed only in their route of administration. Three hundred forty-four healthy post-menopausal women were randomised to six months treatment with either a transdermal matrix patch containing 25 µg 17 β -estradiol/125 µg norethisterone acetate (NETA) applied every 3–4 days, or an equivalent oral preparation (estradiol 1mg and NETA 0.5 mg given once daily). Oral treatment significantly reduced fibrinogen (p<0.003), factor VIIc (FVIIc) (p<0.00001), and antithrombin (AT) levels (p<0.005); the effects in the transdermal group were less marked with no reduction in fibrinogen levels and lesser effect on FVIIc (p<0.03) compared with oral treatment. Treatment type significantly affected fibrinolysis with lower plasminanti- plasmin (PAP) levels in the transdermal group (p<0.003) and lower plasminogen activator inhibitor-1 antigen (PAI-1) (p<0.012) and tissue plasminogen activator (tPA) antigen levels in the oral group (p<0.002). Prothrombin fragment 1.2 and activated protein C (APC) resistance were not affected by either treatment. Transdermal HT has a less marked effect on coagulation than an equivalent oral preparation. Randomised trials are required to investigate whether this translates into less risk of cardiovascular and thromboembolic disease.
Keywords: Transdermal hormone therapy; coagulation; fibrinolysis; menopause